Analisys Of Factors Affecting Customer Satisfaction and Loyality Of Mobile Banking At Private Bank Company - Arif Kurniawan; Jarot S.Suroso (UniSadhuGuna Business School, 2023)
Retaining customers is considered important compared to attracting new customers, because it can be considered cheaper than attracting customers who have left, customer loyalty will reduce bank costs to find new customers. Therefore, customer satisfaction and loyalty are very important for the banking world. This can be measured using the TAM method. Customers will be very satisfied and loyal to a bank, but will also quickly move to another bank that can provide better satisfaction than other banks. For this reason, it is necessary to periodically improve mobile banking service facilities as factors of customer interest in performing self-service.